2011
DOI: 10.3310/hta15030
|View full text |Cite
|
Sign up to set email alerts
|

MAVARIC – a comparison of automation-assisted and manual cervical screening: a randomised controlled trial

Abstract: An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per issue and for the rest of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 71 publications
3
45
2
Order By: Relevance
“…Despite the fact that relevant studies [13,17,18,27,28,29,30] have been published since the last European guidelines, our previous conclusion did not change: we consider the two techniques as equivalent in terms of efficacy.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Despite the fact that relevant studies [13,17,18,27,28,29,30] have been published since the last European guidelines, our previous conclusion did not change: we consider the two techniques as equivalent in terms of efficacy.…”
Section: Discussionmentioning
confidence: 77%
“…Regarding the efficacy of computer cytology, we updated the review reported in the EU guidelines [10] and founded 6 new relevant studies: 4 trials [13,17,18,27,28] and 2 double testing studies [29,30]. The latter group of studies compared computer-assisted LBC versus conventional manual Pap smear; no differences were reported (both the techniques identified all the 9 high-grade lesions) in one study [30] and a 19% increase in detection rate was reported in the other [29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations